2020
DOI: 10.1007/s40544-020-0410-3
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity achieved with two-dimensional nano-additives to liquid lubricants

Abstract: The topic of superlubricity is attracting considerable interest around the world while humanity is facing an energy crisis. Since various liquid superlubricity systems can be commonly achieved on the macroscale in ambient conditions, it is considered an effective solution to reduce unnecessary energy and material losses. However, certain practical problems such as low load-bearing pressure, dependence on hydrogen ions, and relatively long running-in processes still limit its widespread application. Twodimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 90 publications
0
44
0
Order By: Relevance
“…Given recent innovative progress in reducing friction and wear, superlubricity, defined as a friction coefficient (COF) of less than 0.01, is considered a viable strategy [4]. Nowadays, superlubricity, including solid superlubricity [5] and liquid superlubricity [6], has attracted continuously attention in many fields including machinery, energy, aerospace, and biology [7][8][9][10]. As for solid superlubricity, the achievement of extremely low COF (< 0.01) usually relied on a specific structure (e.g., graphite, MoS 2 , a-C:H, and diamond like carbon (DLC) film) [11][12][13][14][15] or a certain atmosphere (e.g., inert gas and vacuum) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given recent innovative progress in reducing friction and wear, superlubricity, defined as a friction coefficient (COF) of less than 0.01, is considered a viable strategy [4]. Nowadays, superlubricity, including solid superlubricity [5] and liquid superlubricity [6], has attracted continuously attention in many fields including machinery, energy, aerospace, and biology [7][8][9][10]. As for solid superlubricity, the achievement of extremely low COF (< 0.01) usually relied on a specific structure (e.g., graphite, MoS 2 , a-C:H, and diamond like carbon (DLC) film) [11][12][13][14][15] or a certain atmosphere (e.g., inert gas and vacuum) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Ge et al [30] utilized the induced tribochemical reaction to situ-form ionic liquids (ILs) on ceramic interfaces and achieved ultralow COF (0.003) and excellent antiwear properties. Other studies on liquid superlubricity have been reported, including the aqueous lubrication of charged polymer brushes [31], in situ formation of tribofilm with MXene nanoflakes in glycerol, the synergistic effect of graphene-oxide nanoflakes and ethanediol [32], IL-modified carbon quantum dots (CQDs) [33], two-dimensional nanoadditives [6], and macromolecular structures [34].…”
Section: Introductionmentioning
confidence: 99%
“…Black phosphorus (BP) is emerging as a unique material and has attracted much scientific attention [121,122]. In particular, BP exhibits weak interlayer interactions, an anisotropic lamellar structure, high thermal stability, a tunable bandgap, and high carrier mobility; this makes it suitable as a liquid lubricant additive in numerous applications, including tribology [123][124][125].…”
Section: Black Phosphorusmentioning
confidence: 99%
“…Spencer et al used the chemical grafting method to graft a poly­(methacrylic acid) brush (anionic polymers) onto Si/SiO 2 substrates, and the friction coefficient was lower than 0.005 under a low-contact pressure . In addition to anionic polymers, poly­(2-(dimethylamino)­ethyl methacrylate) is widely studied as a cationic polymer because it is protonated with the positive charge under acidic conditions, leading to the achievement of superlubricity (friction coefficient < 0.01). − Although the lubrication performance of charged polymer brushes was good, the charged polymer brushes usually have poor biocompatibility resulting from the biofouling problem, which, in turn, increases the surface friction, greatly limiting the applications …”
Section: Introductionmentioning
confidence: 99%